Social adjustment of teenage boys in a residential home - Goh, Daniel Dominic Oon Sye. (2008)
A study was carried out to investigate the social adjustment of adolescent males. Two samples of boys were selected, one from a residential home and one from a secondary school. In all, data of 130 subjects were used, of which 77 were male adolescents living in the residential home and 53 were male adolescents studying in the secondary school. A thrity-five item survey questionnaire was formulated as the instrument for data collection. Five scales in the questionnaire was used to measure social adjustment based on the five research questions pertaining to the perception of teacher support, the perception of peer support, the sense of belonging to school, the attitude towards education, and the perception of family bonding.